Errors Made by The Presenters of Thesis Proposal Seminar in English Study Program - Aziz, Jalal Abdul (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2014)
This study is aimed to find out the types of errors made by the presenters of thesis proposal seminar based on Communicative Effect Taxonomy and to find out whether or not global errors of Communicative Effect Taxonomy made by the presenters of thesis proposal seminar significantly hinder communication between the presenters and the audiences. This study used qualitative approach since the data of this study was taken from 4 students' presentations which were in the form of words rather than number and statistic. This study revealed that there were 188 errors committed by the students in which 179 and 9 erroneous utterances fall under local error and global error respectively. The local errors consist of 45 lexical errors, 93 morphological errors, and 41 syntactical errors. The global errors consist of 2 wrong order of major constituents, 1 missing, wrong, or misplaced sentence connectors, 1 missing, wrong, or misplaced sentence connectors, and 5 uncategorized global errors. As for the effect of global error to the audience, the writer found out that the global errors did not significantly hinder communication to the audience.